Unexpected Routes of the Mutagenic Tautomerization of the T Nucleobase in the Classical A·T DNA Base Pairs: A QM/QTAIM Comprehensive View - Brovarets', Ol'ha O.; Tsiupa, Kostiantyn S.; Dinets, Andrii; Hovorun, Dmytro M. (Frontiers in Chemistry, 2018)
In this paper using quantum-mechanical (QM) calculations in combination with Bader's quantum theory of “Atoms in Molecules” (QTAIM) in the continuum with ε=1, we have theoretically demonstrated for the first time that revealed recently highly-energetic conformers of the classical А∙Т DNA base pairs – Watson-Crick (A∙T(wWC)), reverse Watson-Crick (A∙T(wrWC)), Hoogsteen (A∙T(wH)) and reverse Hoogsteen (A∙T(wH)) – act as intermediates of the intrapair mutagenic tautomerization of the T nucleobase owing to the novel tautomerisation pathways: A∙T(wWC)↔A∙T*(w⊥WC); A∙T(wrWC)↔A∙T*O2(w⊥rWC); A∙T(wH)↔A∙T*(w⊥H); A∙T(wrH)↔A∙T*O2(w⊥rH). All of them occur via the transition states as tight ion pairs (A+, protonated by the N6H2 amino group)∙(T-, deprotonated by the N3H group) with quasi-orthogonal geometry, which are stabilized by the participation of the strong (А)N6+H∙∙∙O4-/O2-(Т) and (А)N6+H∙∙∙N3-(Т) H-bonds. Established tautomerizations proceed through a two-step mechanism of the two-step protons moving in the antiparallel directions along the intermolecular H-bonds. Initially, single proton moves from the N3H imino group of T to the N6H2 amino group of A and then subsequently from the protonated N6+H3 amino group of A to the О4/О2 oxygen atom of Т, leading to the products – A∙T*(w⊥WC), A∙T*O2(w⊥rWC), A∙T*(w⊥H) and A∙T*(w⊥rH), which are substantially non-planar, conformationally-labile complexes. These mispairs are stabilized by the participation of the (А)N6H/N6H´∙∙∙N3(Т) and (Т)O2H/O4H∙∙∙N6(А) H-bonds, for which the pyramidalized amino group of A is their donor and acceptor. The Gibbs free energy of activation of these mutagenic tautomerizations lies in the range of 27.8-29.8 kcal∙mol-1 at T=298.15 K in the continuum with ε=1.